Pre-Transplant Expression of CCR-2 in Kidney Transplant Recipients Is Associated With the Development of Delayed Graft Function - Pontrelli, Paola; Simone, Simona; Rascio, Federica; Pesce, Francesco; Conserva, Francesca; Infante, Barbara; Castellano, Giuseppe; Sallustio, Fabio; Fiorentino, Marco; Zaza, Gianluigi; Gallone, Anna; Battaglia, Michele; et al. (Frontiers in Immunology, 2022)
Background: Delayed graft function (DGF) leads to a reduced graft survival. Donors' features have been always considered as key pathogenic factors in this setting. The aim of our study was to evaluate the recipients' characteristics in the development of DGF. Methods: We enrolled 932 kidney graft recipients from 466 donors; 226 recipients experienced DGF. In 290 donors both recipients presented with early graft function (EGF, group A), in 50 both recipients experienced DGF (group B) and in 126 one recipient presented with DGF and the other with EGF (group C). In group C we selected 7 couples of DGF/EGF recipients and we evaluated transcriptomic profile by microarray on circulating mononuclear cells harvested before transplantation. Results were validated by qPCR in an independent group of 25 EGF/DGF couples. Findings: In the whole study group, DGF was associated with clinical characteristic related to both donors and recipient. In group C, DGF was significantly associated with body mass index, hemodialysis and number of mismatches. In the same group we identified 411 genes differently expressed before transplantation between recipients discordant for the transplant outcome. Those genes were involved in immune dysfunction and inflammation. In particular, we observed a significant increase in DGF patients in the expression of C-C chemokine receptor type 2 (CCR2), the monocyte chemoattractant protein-1 (MCP-1) receptor. CCR-2 up-regulation was confirmed in an independent cohort of patients. Conclusions: Our results suggest that recipients' clinical/immunological features, potentially modulated by dialysis, are associated with the development of DGF independently of donors' features.